2022
DOI: 10.3389/fpsyt.2022.821455
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Prenatal Drug Exposure, Maternal Inflammation, and Parental Aging on the Development of Autism Spectrum Disorder

Abstract: Autism spectrum disorder (ASD) affects reciprocal social interaction and produces abnormal repetitive, restrictive behaviors and interests. The diverse causes of ASD are divided into genetic alterations and environmental risks. The prevalence of ASD has been rising for several decades, which might be related to environmental risks as it is difficult to consider that the prevalence of genetic disorders related to ASD would increase suddenly. The latter includes (1) exposure to medications, such as valproic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 273 publications
(295 reference statements)
1
17
0
Order By: Relevance
“…Lipopolysaccharide (LPS) is a molecule composed of lipids and carbohydrates found on the cell wall surface of Gram-negative bacteria such as Escherichia coli , and mimics bacterial infection to induce inflammation [ 54 ]. LPS is also used a reagent for making animal models of MIA [ 55 ], and it regulates inflammation and immunity by activating downstream signals through toll-like receptor 4 (TLR4) [ 39 , 54 ]. Administration of either LPS or poly(I:C) are commonly used methods to induce MIA, and the phenotype of ASD model animals obtained by both is similar [ 56 ].…”
Section: Mia and Neuroinflammation In Asdmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipopolysaccharide (LPS) is a molecule composed of lipids and carbohydrates found on the cell wall surface of Gram-negative bacteria such as Escherichia coli , and mimics bacterial infection to induce inflammation [ 54 ]. LPS is also used a reagent for making animal models of MIA [ 55 ], and it regulates inflammation and immunity by activating downstream signals through toll-like receptor 4 (TLR4) [ 39 , 54 ]. Administration of either LPS or poly(I:C) are commonly used methods to induce MIA, and the phenotype of ASD model animals obtained by both is similar [ 56 ].…”
Section: Mia and Neuroinflammation In Asdmentioning
confidence: 99%
“…In the preclinical studies of ASD, antioxidant effects have been reported using ASD model animals ( Table 2 ). Valproic acid (VPA) exposure during pregnancy increases the risk of ASD in offspring (VPA mice or rats), which has been widely used as a method for producing ASD model animals [ 10 , 55 ]. In VPA-induced ASD model mice, HRW administration improved ASD-like behaviors such as social behavior and pain sensation as well as anxiety-like behavior and memory impairment and IL-6 and TNF-α inflammatory cytokines [ 183 ].…”
Section: Preclinical Studies Of Antioxidants In Asd Model Animalsmentioning
confidence: 99%
“…The major citing documents for Clusters #4 and #6 are authored by St. Clair and Johnstone [ 108 ] (coverage = 22; GCS = 13) and Lord et al [ 109 ] (coverage = 23; GCS = 211), respectively. While Clusters #4 and #6 were originally labelled “Valproic Acid” and “Brain Organoid”, respectively, a more representative label for both clusters may be “Stem Cell Technology”, as papers in the two clusters focus on the exposure of stem cells to various molecules, including valproic acid (a molecule that is associated with higher likelihood of developing ASD [ 110 ]), to investigate the development of ASD-like phenotypes [ 108 , 111 , 112 , 113 , 114 ]. Papers in Cluster #4 use stem cells to mimic the prenatal development processes in order to trace the pathogeneses of ASD.…”
Section: Discussionmentioning
confidence: 99%
“…The various non-genetic elements mediating ASD risk comprise of parental age, maternal nutritional status, infections during pregnancy, and exposure to certain toxins, heavy metals, or drugs [ 30 ]. Clinical investigations reveal an imbalance in the microbiota of ASD individuals [ 31 ].…”
Section: Introductionmentioning
confidence: 99%